Paracoccidioidomycosis in the spine: case report and review of the literature - Alvarenga, José Alexandre Lopes da Silva; Martins, Délio Eulálio; Kanas, Michel; Elizeche, Hugo Gustavo Kunzle; Dell’Aquila, Adriana Macêdo; Fernandes, Eloy De Avila; Wajchenberg, Marcelo; Puertas, Eduardo Barros (São Paulo Medical Journal, 2016)
CONTEXT: Paracoccidioidomycosis is a systemic form of mycosis that spreads hematogenously, secondarily to reactivation of lung infection or infection at another site or to new exposure to the causative agent. Few cases of bone involvement have been reported in the literature and involvement of the spine is extremely rare. CASE REPORT: We describe a case of a 68-year-old male patient with spondylodiscitis at the levels L4-L5 caused by presence of the fungus Paracoccidioides brasiliensis, which was diagnosed through percutaneous biopsy. The patient was treated with sulfamethoxazole and trimethoprim for 36 months, with complete resolution of the symptoms. CONCLUSION: Spondylodiscitis caused by the fungus Paracoccidioides brasiliensis is uncommon. However, in patients with chronic low-back pain who live or used to live in endemic regions, this infection should be considered as a possible differential diagnosis.